The effect of nitrate supplementation on cycling performance in the heat in well-trained cyclists - McQuillan, J. A.; Casadio, J. R.; Dulson, D. K.; Laursen, P. B.; Kilding, A. E. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine the effect of NO3-consumption on measures of perception, thermoregulation, and cycling performance in hot conditions. Methods: In a randomized, double-blind, crossover design, 8 well-trained cyclists (mean±SD age 25±8 y, V.O2 peak 64±5 mL/kg·min) performed 2 separate trials in hot (35°C, 60% relative humidity) environments, having ingested either 140 mL NO3--rich beetroot juice ~8 mmol NO3- (NIT) or placebo (PLA) daily for 3 d with a 7-d washout period separating trials. Trials consisted of 2×10-min bouts at 40% and 60% peak power output (PPO) to determine physiological and perceptual responses to the heat, followed by a 4-km cycling time trial. Results: Basal [nitrite] was substantially elevated in NIT (2.70±0.98 µM) vs PLA (1.10?±?0.61 µM), resulting in a most likely (ES=1.58±0.93) increase after 3 d. There was a very likely trivial increase in rectal temperature in NIT at 40% (PLA 37.4°C±0.2°C vs NIT 37.5°C±0.3°C, 0.1°C±0.2°C) and 60% (PLA 37.8°C±0.2°C vs NIT 37.9°C±0.3°C, 0.1°C±0.2°C) PPO. Cycling performance was similar between trials (PLA 336±45 W vs NIT 337±50 W, CV±?95%CL; 0.2%±2.5%). Outcomes for heart rate and perceptual measures were unclear across the majority of time points. Conclusions: Three days of NO3-supplementation resulted in small increases in rectal temperature during low- to moderate-intensity exercise, but this did not appear to influence 4-km cycling time-trial performance in hot climates.